Application of Chopper Machinery Technology from Oil Palm Fronds in Huta Gondang Rejo Nagori Bandar Tongah Bandar Hands, Regency of Simalungun - Ariani, Farida; Tugiman; Tafsin, Ma'ruf; Susilo, Hariadi; Bayu, Eva Sartini; Tulus (Journal of Saintech Transfer, 2018)
This community service activity aims to improve the efficiency of cattle farm business in Huta Gondang Rejo Nagori Bandar Tongah Bandar Huluan Subdistrict Simalungun Regency through the use of pellet complete feed based on palm oil fronds and agricultural waste. This activity is conducted on cattle ranchers who are members of the farming community group Huta Gondang Rejo. Farmers are given counseling and training on the processing of palm oil fronds and agricultural waste into livestock feed and the establishment of a complete ration of palm-based pellet and agricultural waste. To facilitate the transfer of this technology to the breeder, then prepared a complete feed pellet with 5 types of machines. Palm Crusher Counter Machines or Palm Crafter Engines with a capacity of 600 kg/hour. Pellet printing machine (granulator) with capacity of 100 kg/hour. Mixer machine (mixer feed) with a capacity of 50 kg/stir. Dryer (Oven) with capacity of 10 kg/rack. Manual press feed press tool with specification 2 kg/print. Measuring the success of this activity is seen from the level of farmer adoption of pelleting technology and the difference of ration conversion between cattle that get complete feed and conventional or traditional. Performance of palm cropping machine for cattle that get complete pellet feed is better than cattle that get conventional or traditional feed. This Chopper machine can count the palm stem from the tip of the base of the leaf to the stem (80% of the palm stem). Through the activities of plant waste feed technology is expected to achieve some outcomes, namely, improve the productivity of farming through the system integration of livestock combine farming system with synergistic system to form an effective, efficient and environmentally friendly.